2020
DOI: 10.1177/0972150920973504
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Psychology Behind Panic Buying: A Grounded Theory Approach

Abstract: A psychological phenomenon that has triggered panic buying by the rapid spread of emergent epidemic is worthy of consideration. Population across cultures and national boundaries has raided shops at each growth stage of this epidemic, and India’s fast-moving consumer goods companies have faced increased pressure to ramp up production to meet demand. Limited research in consumer behaviour theory has approached to this collective action of panic buying or in other terms stockpiling. A theory needs to be develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 30 publications
0
44
0
1
Order By: Relevance
“…Additionally, other studies reported that PB was more common among people who were more worried about the COVID-19 pandemic and that social media possibly played a role in disseminating the worry, fear, and anxiety by showing images of empty shelves, which in turn produced a sense of scarcity and short supply (19)(20)(21). Studies from different settings have also reported that rumors regarding the shortage of supplies increased PB (22)(23)(24).…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…Additionally, other studies reported that PB was more common among people who were more worried about the COVID-19 pandemic and that social media possibly played a role in disseminating the worry, fear, and anxiety by showing images of empty shelves, which in turn produced a sense of scarcity and short supply (19)(20)(21). Studies from different settings have also reported that rumors regarding the shortage of supplies increased PB (22)(23)(24).…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…In a reaction of fear to perceived and real scarcity, this sudden change in consumer behavior occurs in emergencies as a mass psychological phenomenon looking for survival. However, consumers accumulation of products on a large scale results in a lack of product supply in the market and a consequent increase in average prices (ANASTASIADOU et al, 2020; ANTONIDES; VAN LEEUWEN, 2020;BARNES et al, 2020;DONTHU;GUSTAFSSON, 2020;KAUR;MALIK, 2020;KIRK;RIFKIN, 2020;LI et al, 2020;LOXTON et al, 2020;PRENTICE et al, 2020;ELLISON et al, 2021).…”
Section: Panic Buying: Food and Other Products Stock During The Pandemicmentioning
confidence: 99%
“…Other epidemics were experienced in the past, and many restrictions that brought difficulties were imposed previously, such as restrictions on trade, movement of people and goods, limitations on exports, and interruptions in production (HASSAN et al, 2020;KAUR;MALIK, 2020). Public health organizations and experts in the field warned, in 2017, that the emergence of a new pandemic would be close and that no nation would be fully prepared to face it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous COVID-19 research suggests pandemic panic buying is driven by the economic factor in COVID-19 phobia including worries about shortages ( Kaur and Malik, 2020 ) and fears of associated price increases ( Arafat et al, 2020c ). First, people may amass excessive amounts of supplies to avoid feeling unprepared.…”
Section: Introductionmentioning
confidence: 99%